Editorial - Eugenia Ellanskaya (Slovo, 2014)
Slovo is a peer-reviewed interdisciplinary academic journal run by postgraduate students at the School of Slavonic and East European Studies, University College London. Spanning across humanities and social sciences, the journal covers all issues concerning Russia, Eurasia, Central and Eastern Europe. While seeking to provide a publishing opportunity both to outstanding young researchers and established academics, Slovo is a unique voice for the regions covered. In our third year as a digital publication, we hope to reach out to a wider audience and to continue sharing our academic discoveries internationally. Click here to read article